Experimental and theoretical investigation on synchronization of a vibration system flexibly driven by two motors. (July 2020) - Li, Yujia; Ren, Tao; Meng, Xiaoping; Zhang, Minghong; Zhao, Peng
With the increasing requirements for screening new materials, such as high-density and high-viscosity drilling fluids, it is necessary to increase the exciting force of the shale shaker to fully handle the new materials. To increase the exciting force of shale shaker while improving the force condition, a dynamic model of a vibration system flexibly driven by two motors is proposed in this paper. The dynamic behavior and synchronization theory of this system are investigated by using Lagrange equation and Hamilton's principle. The calculation proves that the conventional planar vibration system rigidly driven by two motors is a special case of the investigated spatial vibration system flexibly driven by two motors. The phase difference between the eccentric rotors is automatically adjusted by the system to balance the change in the motor installation position for maintaining synchronization and stability. Theoretical investigation and experimental verification prove that the system can synchronize vibration without additional control synchronization.